Preemptive market exploitability: resource advantage theory of competition perspective - Situmorang, Tumpal Pangihutan; Ferdinand, Augusty Tae; Indriani, Farida (Business: Theory and Practice, 2024)
The current study aims to elucidate the critical importance of preemptive market exploitability as a bridging concept for solving the inconsistent findings on the role of entrepreneurial orientation in enhanced marketing performance. Rooted on the resource advantage theory of competition (RAToC), the preemptive move is postulated as a strategic orientation for reaching a competitive positional advantage in the market when supported by a strong entrepreneurial orientation complemented with a solid quality-based differentiation. A survey method was used to collect data after inviting four hundred owner-managers of small and medium enterprises (SMEs) to participate in this study. The structural equation modelling software AMOS tested our proposed hypotheses. The quantitative analysis resulted in accepting the proposed premises with several significant findings. The most important finding is that companies should invest in preemptive market exploitability as a strategic asset for high marketing performance.